Epistemology of Hadith: Orientation for Chapters Compilation in the Kutub Sittah - Ulama'i, Hasan Asy'ari; Muhtarom, Muhtarom; Mundhir, Mundhir (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2022)
This paper examines the epistemology of hadith, namely the orientation and background of the arrangement of the